One- and Six-month Outcomes of Patients with Non-ST Elevation Myocardial Infarction - Hossein Vakili; Roxana Sadeghi; Neda Toofaninejad; Tooba Akbari; Naser Kachoueian (Publisher: Shahid Beheshti University of Medical Sciences, 2016)
Introduction: Use of risk scoring systems in patients with acute coronary syndrome helps with summarizing important prognostic data of the disease and facilitates calculating confidence limits and comparing survival rates between different treatments. In the present study, the researchers first aimed at assessing mid-term outcome of patients with non-ST elevation myocardial infarction (NSTEMI), and then determining main predictors of this outcome to improve definitive criteria for designing a risk scoring system in the population.Methods: In a prospective cohort study, 124 patients with NSTEMI, diagnosed according to ACC/AHA guidelines and hospitalized in an academic hospital in 2013, were consecutively assessed. Baseline characteristics were collected via interviewing, physical examination, and reviewing the recorded files. All the patients were followed for one and six months to assess mid-term outcomes regarding mortality and major adverse cardiac events (MACE). MACE is defined as the occurrence of at least one of the events of death, myocardial infarction, repeated revascularization, or re-hospitalization.Results: One-month death occurred in 3.2%, re-hospitalization in 4.0%, and myocardial infarction in none of the patients. In addition, regarding the six-month outcomes status, mortality rate was determined in 6.4%, re-hospitalization in 22.6%, and myocardial infarction in 4.8% of patients. Hence, one- and six-month MACE rates were 7.3% and 27.4%, respectively. Furthermore, three- and six-month survival rates were estimated to be 96.8% and 93.6%, respectively. According to the Cox-proportion hazard modeling, only reduced left ventricular ejection fraction (LVEF) (HR = 0.909, P = 0.017), history of chronic kidney injury (HR = 8.884, P = 0.005), and Inotrope use (HR = 35.759, P = 0.012) could predict the six-month MACE. None of the other indexes including general coronary risk factors, echocardiography parameters, and level of cardiac enzymes could predict mortality rate.Conclusions: Patients with NSTEMI may face high six-month MACE which can be predicted by low LVEF, history of renal injury and use of inotrope. Therefore, to define risk stratification system, these indicators should be considered as well.